English

Find X and Y, If 3(1, 2, 0), (0, -1, 3) - (1, 5, -2), (-3, -4, 4) (1), (2), (1) = (X), (Y) - Mathematics and Statistics

Advertisements
Advertisements

Question

Find x and y, if 
`{ 3[(1, 2, 0), (0, -1, 3)] - [(1, 5, -2), (-3, -4, 4)]}[(1), (2), (1)] = [(x), (y)]`

Sum

Solution

`{ 3[(1, 2, 0), (0, -1, 3)] - [(1, 5, -2), (-3, -4, 4)]}[(1), (2), (1)] = [(x), (y)]`

`[(2, 1, 2), (3, 1, 5)] [(1), (2), (1)] = [(x), (y)]`

`[(6), (10)] = [(x), (y)]`

∴ x = 6 and y = 10

shaalaa.com
  Is there an error in this question or solution?
2015-2016 (March)

APPEARS IN

Video TutorialsVIEW ALL [1]

Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×